Racial and Ethnic Inequities in Postpartum Pain Evaluation and Management. Issue 6 (December 2019) - Johnson, Jasmine D.; Asiodu, Ifeyinwa V.; McKenzie, Christine P.; Tucker, Christine; Tully, Kristin P.; Bryant, Katherine; Verbiest, Sarah; Stuebe, Alison M.
Abstract : OBJECTIVE: To evaluate whether the frequency of pain assessment and treatment differed by patient race and ethnicity for women after cesarean birth. METHODS: We performed a retrospective cohort study of all women who underwent cesarean birth resulting in a liveborn neonate at a single institution between July 1, 2014, and June 30, 2016. Pain scores documented and medications administered after delivery were grouped into 0–24 and 25–48 hours postpartum time periods. Number of pain scores recorded, whether any pain score was 7 of 10 or greater, and analgesic medication administered were calculated. Models were adjusted for propensity scores incorporating maternal age, body mass index, gestational age, nulliparity, primary compared with repeat cesarean delivery, classical hysterotomy, and admission to the neonatal intensive care unit. RESULTS: A total of 1, 987 women were identified, and 1, 701 met inclusion criteria. There were 30, 984 pain scores documented. Severe pain (7/10 or greater) was more common among black (28%) and Hispanic (22%) women than among women who identified as white (20%) or Asian (15%). In the first 24 hours after cesarean birth, non-Hispanic white women had more documented pain assessments (adjusted mean 10.2) than, black, Asian, and Hispanic women (adjusted mean 8.4–9.5; P <.05). Results at 25–48 hours were similar, compared with non-Hispanic white women (adjusted mean 8.3). Black, Asian, and Hispanic women and women who were identified as other all received less narcotic medication at 0–24 hours postpartum (adjusted mean 5.1–7.5 oxycodone tablet equivalents; P <.001–.05), as well as at 25–28 hours postpartum. CONCLUSION: Racial and ethnic inequities in the experience, assessment and treatment of postpartum pain were identified. A limitation of our study is that we were unable to assess the role of patient beliefs about expression of pain, patient preferences with regards to pain medication, and beliefs and potential biases among health care providers. Abstract : We found race and ethnicity inequities in the experience, assessment, and management of postcesarean delivery pain.